Dopamine (DRD2) and Serotonin (HTR2A, 2C) Receptor Gene Polymorphisms do not influence early response to Risperidone in South Indian Patients with Schizophrenia. (21st November 2018) - Alladi, Charanraj Goud; RajKumar, Ravi Philip; Adithan, Surendiran; Marie‐Claire, Cynthia; Bellivier, Frank; Shewade, Deepak Gopal
Abstract: Treatment response to antipsychotic drugs is variable and conflicting results have been obtained while studying the influence of DRD2 and HTR2 genetic variants on antipsychotic drug efficacy. To explore further, the present study aimed to assess the influence of DRD2 ‐141 C Ins/Del, Taq1A and HTR2A ‐1438 G/A, 102T/C and HTR2C ‐759 C/T genetic polymorphisms in response to risperidone in patients with schizophrenia. The study was conducted among the n = 320 South Indian patients with schizophrenia who received risperidone treatment (4–8 mg per day) for a minimum of four weeks. Genotyping was done by real‐time PCR. Antipsychotic response was assessed using CGI‐I score in cross‐sectional group, PANSS score in prospective group at baseline and after receiving the risperidone therapy. DRD2 ‐141 C Ins/Del ( n = 310, Ins/Ins = 177, Ins/Del+ Del/Del = 133, OR 0.70, 95% CI 0.4–1.2 p 0.2), Taq1A ( n = 320, AA = 35, AG = 132, GG = 153, p 0.2), HTR2A ‐ 1438 G/A ( n = 320, AA = 39, AG = 164, GG = 117, p 0.2), HTR2A 102T/C ( n = 320, CC = 115, CT = 165, TT = 40, p 0.1) HTR2C ‐ 759 C/T (females n = 132, CC = 65, CT+TT = 67, OR 1.3, 95% CI 0.6–2.8, p 0.5; males n = 186, C = 120, T = 66, OR 1.2, 95% CI 0.6–2.4, p 0.4) genetic polymorphisms did not show any association with antipsychotic response to risperidone. DRD2 ‐141 C Ins/Del, Taq1A, HTR2A ‐1438 G/A, 102T/C and HTR2C ‐759 C/T genetic variants are not associated with antipsychotic response to risperidone.